Potential of Combination of Garlic Extract and Polyphenols as a Curative Method for Controlling Ganoderma boninense - Achmad Yusup, Ciptadi; Dewantara Eris, Deden; Sri Mulyatni, Agustin; Gama Pradana, Mahardika; Widiastuti, Happy; Santoso, Djoko (Jurnal Penelitian Kelapa Sawit, 2024)
Basal stem rot (BSR) disease control is currently focused on preventive activities, and curative control techniques are needed to complement existing preventive methods. The use of organic fungicides is an environmentally friendly solution. Garlic extract (GE) and polyphenols (P) have antifungal activities against various types of fungi. Combining these two mixtures was expected to create a synergistic interaction that effectively controls G. boninense curatively. This research aimed to evaluate the antifungal activity of the combination of GE and P (GE+P) against G. boninense, determine the optimum concentration for killing G. boninense in vitro, and formulate an organic fungicide from GE+P. In vitro assay was conducted using a poisoned food technique, and the compatibility test was done using a checkerboard assay method. Evaluation of growth capacity of treated G. boninense inoculum was evaluated through the Bavendamm test. The curative effect of GE+P combination was assessed by droplet and spraying assay on the colony of G. boninense. The destruction of G. boninense mycelium was observed with a scanning electron microscope (SEM). The research results indicate that the combination of GE+P exhibits a synergistic interaction and can damage G. boninense mycelium tissue at a minimum concentration of 0.4%. SEM observations reveal severe damage to G. boninense mycelium tissue at a concentration of 1.6%. The formulation of organic fungicide combination of GE+P successfully produces a homogenous and stable solution with the addition of sodium lauryl sulfate (SLS) surfactant. Shelf-life testing of the organic fungicide formulation shows stability and no reduction of effectiveness after being stored for six months.